Mengungkap Budaya Baru Penyiaran Radio: Analisis Perubahan dalam Produksi, Distribusi, dan Konsumsi Program Radio - Ronny Yudhi Septa Priana; Dian Wardiana Sjuchro; Rina Fitriana (Society, 2025)
This study explores the emergence of a new culture within the radio broadcasting industry, focusing on transformations in radio programs' production, distribution, and consumption. The new culture refers to shifts driven by digital transformation, significantly altering media practices. While previous studies have largely examined digitalization in mainstream or commercial media, little attention has been given to its impact on government-owned and community-based radio stations. To address this gap, the study employs a qualitative case study approach, examining two local broadcasting institutions in Indonesia: Serang Gawe FM, a Local Public Broadcasting Institution (LPBI; Lembaga Penyiaran Publik Lokal or LPPL) operated by the Serang Regency Government, and TiRTA FM, a student-run community radio station at Sultan Ageng Tirtayasa University. Data were collected through in-depth interviews and limited participatory observation, and analyzed through coding and thematic interpretation. Findings reveal that integrating internet-based technologies and social media has introduced new cultural practices in broadcasting. These include using social media to promote programs, conduct live streams, and distribute content via audio streaming platforms, resulting in greater audience reach and enhanced interactivity. The digital transformation has redefined the roles of broadcasters and listeners, fostering more participatory and dynamic communication. Furthermore, it enables local radio stations to connect with audience segments beyond the limitations of traditional FM signal coverage. This study contributes to ongoing discussions on media convergence and digital transformation by demonstrating that these developments are both technological and cultural. It emphasizes the importance of institutional adaptability and highlights the evolving relationship between media producers and audiences in the digital era.